PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE STAD BERBANTUAN GEOGEBRA TERHADAP KEMAMPUAN BERPIKIR KRITIS MATEMATIS PESERTA DIDIK KELAS IX SMP NEGERI 28 PADANG - Fitri, Wimpi Widia (Jurnal Edukasi dan Penelitian Matematika, 2023)
Students need critical thinking, creativity, collaboration, and communication abilities in the 21st century. However, class IX SMP Negeri 28 Padang pupils still lack mathematical critical thinking. The STAD learning approach using GeoGebra was selected. This research examined whether students' mathematical critical thinking skills are better when using the STAD type cooperative learning approach using GeoGebra than when studying directly in class IX SMP Negeri 28 Padang. This is a Nonequivalent Posttest-Only Control Group Design pseudo-experiment. Simple Random Sampling was used. After the draw, class IX.2 was the experimental class and class IX.1 the control class. Questionnaires and tests of mathematical critical thinking were employed for study. This study's hypothesis was proven using the t test. The P-value was 0.000 after data analysis. As the P-value is < α = 0.05, H0 is discarded. Students that use the STAD learning paradigm with GeoGebra have greater mathematical critical thinking skills than those who use direct learning.Keywords– STAD, Mathematical Critical Thinking Skills, Geogebra, Direct Learning.